A review on the future of internet of things (Iot) in higher education - Owobu, Izehi; Md Khambari, Mas Nida (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Internet of Things (IoT) is the next era of connectivity which allows physical objects being embedded with sensors to connect to the internet and exchange information with each other. The application of IoT in education is a new wave of change that is massively improving both teaching and learning process and educational institutions. It has great potential for use in the institution of higher education and will shape the learning experience in numerous ways. This paper discusses the uses of IoT in the higher education, the impact of the internet of things (IoT) in higher education for the next generation and the challenges it poses.